TO ADVENTURES BASED ON EXPERIENCES ORGANIZE IN REACHING METHODICAL - DIDACTIC ANALYSIS - Yunusova Diloramkhan Abdumajitovna (Web of Journals Publishing, 2024)
To adventures based on experiences organize of reaching methodical and didactic supply organize in reaching teachers and coaches for while moving or school students with practical training organize in reaching useful to be can
Keywords: reflection , cooperation , mentorship , aspect.